Motivational Salience Modulates Hippocampal Repetition Suppression and Functional Connectivity in Humans - Zweynert, Sarah; Pade, Jan Philipp; Wüstenberg, Torsten; Sterzer, Philipp; Walter, Henrik; Seidenbecher, Constanze I.; Richardson-Klavehn, Alan; Düzel, Emrah; Schott, Björn H. (Frontiers in Human Neuroscience, 2011)
Repetition suppression (RS) is a rapid decrease of stimulus-related neuronal responses upon repeated presentation of a stimulus. Previous studies have demonstrated that negative emotional salience of stimuli enhances RS. It is, however, unclear how motivational salience of stimuli, such as reward-predicting value, influences RS for complex visual stimuli, and which brain regions might show differences in RS for reward-predicting and neutral stimuli. Here we investigated the influence of motivational salience on RS of complex scenes using event-related fMRI. Thirty young healthy volunteers performed a monetary incentive delay (MID) task with complex scenes (indoor vs. outdoor) serving as neutral or reward-predicting cue pictures. Each cue picture was presented three times. In line with previous findings, reward anticipation was associated with activations in the ventral striatum, midbrain, and orbitofrontal cortex (OFC). Stimulus repetition was associated with pronounced repetition suppression in ventral visual stream areas like the parahippocampal place area (PPA). An interaction of reward anticipation and repetition suppression was specifically observed in the anterior hippocampus, where a response decrease across repetitions was observed for the reward-predicting scenes only. Functional connectivity analysis further revealed specific activity-dependent connectivity increases of the hippocampus and the PPA and OFC. Our results suggest that hippocampal repetition suppression is sensitive to reward-predicting properties of stimuli and might therefore reflect a rapid, adaptive neural response mechanism for motivationally salient information.